2000
DOI: 10.1086/315512
|View full text |Cite
|
Sign up to set email alerts
|

Virologic Analysis of Non‐B, Non‐C Hepatocellular Carcinoma in Japan: Frequent Involvement of Hepatitis B Virus

Abstract: Serum and liver tissues from hepatitis B surface antigen-negative/anti-hepatitis C virus (HCV)-negative (non-B, non-C) hepatocellular carcinoma (HCC) patients in Japan were examined for the presence of hepatitis B virus (HBV), HCV, and TT virus (TTV) by polymerase chain reaction. The studies evaluated the contribution of these viruses to pathogenesis of HCC. HBV DNA was detected in the sera of 20 (47.6%) of 42 non-B, non-C HCC patients, which was significantly higher than in age-matched controls without liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
89
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 40 publications
4
89
2
Order By: Relevance
“…Other patients may have chronic HBV infection for decades leading to liver damage but HBsAg is no longer detectable when cirrhosis or HCC is diagnosed. [19][20][21] The role of occult HBV infection in the etiology of liver disease in seronegative individuals is less clear. Data are scanty and based on case reports or case series.…”
mentioning
confidence: 99%
“…Other patients may have chronic HBV infection for decades leading to liver damage but HBsAg is no longer detectable when cirrhosis or HCC is diagnosed. [19][20][21] The role of occult HBV infection in the etiology of liver disease in seronegative individuals is less clear. Data are scanty and based on case reports or case series.…”
mentioning
confidence: 99%
“…No patients were double-positive for HCV antibody and HBs antigen. Although three patients were double-negative for HCV antibody and HBs antigen, the presence of HBV mRNA was confirmed using the previously reported RT-PCR method (15). These patients were considered to have HBV-positive HCC for further analysis.…”
Section: Methodsmentioning
confidence: 55%
“…These patients were considered to have HBV-positive HCC for further analysis. For the remaining 20 non-B, non-C patients who were double-negative for HCV antibody and HBs antigen, the absence of viral genomes was confirmed by RT-PCR as reported to rule out possible cryptic HCV or HBV infection (15,16). In total, 80 cases were in the HCV group, 19 in the HBV group, and 20 in the non-B, non-C group.…”
Section: Methodsmentioning
confidence: 96%
“…It was reported that the frequency of HCC due to chronic HCV infection is higher in Japan than in any other country (4). Several studies have reported that occult HBV infection may also be one of the causative factors of HCC (5,6). The presence of occult HBV infection is diagnosed based on the fact that HBV DNA still exists in serum and liver tissue after hepatitis B surface antigen (HBsAg) disappears in acute or chronic HBV infection (7)(8)(9), or even after antiviral treatment is successful.…”
Section: Introductionmentioning
confidence: 98%